DAMPAK YURIDIS PERUBAHAN PERATURAN KONTRAK KERJA SAMA HULU MIGAS TERHADAP INVESTASI MIGAS DI INDONESIA: The Juridical Impact Of Changes In Upstream Oil And Gas Production Sharing Contract Regulations On Oil And Gas Investment In Indonesia - Salsabila Indah Safitri; Dian Purnamasari (AMICUS CURIAE, 2025)
Investment plays a crucial role in a country’s economy. Currently, investments have expanded into various sectors, including the oil and gas sector. The implementation of oil and gas investment in Indonesia is based on Production Sharing Contracts (PSC). The prevailing types of PSCs are cost recovery and gross split. The gross split PSC was a new initiative by the government in 2017 aimed at increasing oil and gas investment in Indonesia. However, not long after the gross split PSC was adopted, the government made several regulatory changes regarding oil and gas PSCs, affecting investment activities in the sector and introducing flexibility in the use of PSC types. These frequent regulatory changes have led to uncertainty and doubts among investors. In this context, the identified problem in this study is the legal impact of the regulatory changes to cost recovery and gross split Production Sharing Contracts (PSC) in upstream oil and gas activities. Based on the results and conclusion of the study, it is concluded that the most significant impact of these regulatory changes is legal uncertainty, which disrupts the investment climate and contradicts the principle of legal certainty as stipulated in Law Number 25 of 2007 concerning Investment.